The Library GPII System - Vanderheiden, Gregg C.; Chourasia, Amrish; Tobias, Jim; Githens, Steve (Universal Access in Human-Computer Interaction. Design for All and Accessibility Practice, 2014)
This paper describes the library GPII system (LGS), the first real-world implementation of the GPII (Global Public Inclusive Infrastructure) system. The GPII aims to utilize cloud computing to create the infrastructure to provide affordable assistive services whenever and wherever a user demands them. The interactions of the different stakeholders in the library ecosystem present various challenges to implement such a system. These stakeholders include the library patrons, library staff, government, publishers, software developers and vendors. The development of the LGS will happen in three phases: needs analysis, development and empirical evaluation. Libraries of various sizes and resources will be involved in the development and evaluation of the LGS. We are currently in the first phase and the results of our stakeholder analysis work to-date are presented.